MENINGKATKAN KOMPETENSI PENYUSUNAN LAPORAN KEUANGAN DENGAN MENGGUNAKAN SOFTWARE AKUNTANSI (GURU-GURU DI JAKARTA TIMUR) - Tyas Pambudi Raharjo; Rakendro Wijayanto (Bajang Institute, 2022)
The teacher has a very important role for the progress of education in Indonesia because the teacher is an important factor determining the success of a quality learning process.. To improve the quality of teachers, it is necessary to increase teacher competence, one of which is by increasing the mastery of the material they have. The problem faced by teachers, especially accounting teachers is the lack of information regarding the application of financial statement preparation using accounting software systems so that they can produce report products that can be fast and reliable. This PKM aims to provide counseling and training, the teachers are able to (1) understand the concept of accounting software (2) understand how to identify the types of transactions based on the system module (3) inputting these transactions into the system and displaying the final report. The target of the output of PKM activities is publication in national mass media and campus media, as well as appropriate technology in the form of system-based financial reports